Disorder induced in nonoverlap myosin cross-bridges by loss of adenosine triphosphate. - Padrón, R (1989)
Adenosine triphosphate-dependent changes in myosin filament structure have been directly observed in whole muscle by electron microscopy of thin sections of rapidly frozen, demembranated frog sartorius specimens. In the presence of ATP the thick filaments show an ordered, helical array of cross-bridges except in the bare zone. In the absence of ATP they show two distinct appearances: in the region of overlap with actin, there is an ordered, rigorlike array of cross-bridges between the thick and thin filaments, whereas in the nonoverlap region (H-zone) the myosin heads move away from the thick filament backbone and lose their helical order. This result suggests that the presence of ATP is necessary for maintenance of the helical array of cross-bridges characteristic of the relaxed state. The primary effect of ATP removal on the myosin heads appears to be weaken their binding to the thick filament backbone; released heads that are close to an actin filament subsequently form a new actin-based, ordered array.